Stem Cell Transcription Factor FoxO Controls Microbiome Resilience in Hydra - Mortzfeld, Benedikt M.; Taubenheim, Jan; Fraune, Sebastian; Klimovich, Alexander V.; Bosch, Thomas C. G. (Frontiers in Microbiology, 2018)
The aging process is considered to be the result of accumulating cellular deterioration in an individual organism over time. It can be affected by the combined influence of genetic, epigenetic and environmental factors including life-style associated events. In the non-senescent freshwater polyp Hydra, one of the classical model systems for evolutionary developmental biology and regeneration, transcription factor FoxO modulates both stem cell proliferation and innate immunity. This provides strong support for the role of FoxO as a critical rate-of-aging regulator. However, how environmental factors interact with FoxO remains unknown. Here we find that deficiency in FoxO signaling in Hydra leads to dysregulation of antimicrobial peptide (AMP) expression and that FoxO loss-of-function polyps are impaired in selection for bacteria resembling the native microbiome and more susceptible to colonization of foreign bacteria. These findings reveal a key role of FoxO signaling in the communication between host and microbiota and embed the evolutionary conserved longevity factor FoxO into the holobiont concept.